1996
DOI: 10.1002/elan.1140080417
|View full text |Cite
|
Sign up to set email alerts
|

A photo‐cured calcium ion‐selective electrode for use in flow injection potentiometry that tolerates high perchlorate levels

Abstract: An improved photo-cured membrane selective to calcium was developed based on the calcium bis[4-(l , I ,3,3-tetramethylbutyl)phenyl] phosphate ionophore and incorporates the lipophilic additive, potassium tetrakis(pchloropheny1)borate. The calcium electrode exhibited a hyper-Nernstian response of 31.0 mV change per activity decade and a log-linear range between 1 x lo-' to 0. I M in pure calcium chloride solution, in steady-state mode. The calcium electrode was fast responding, reaching 90% of steady-state valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
0
15
0
4
Order By: Relevance
“…It was, however, reported that their long-term potential stability was limited and they were, therefore, useful only in specific applications such as detectors for capillary electrophoresis [14] or in flow-injection analysis [15]. Their potential instability was attributed to lack of control of the concentrations of the species defining the redox potential at the membrane/metal interface [12,16,17] and their response characteristics were successfully improved by adding an appropriate redox-active component to the PVC membrane [18] or by using an intermediate redox-active polymer layer [19].…”
Section: Introductionmentioning
confidence: 99%
“…It was, however, reported that their long-term potential stability was limited and they were, therefore, useful only in specific applications such as detectors for capillary electrophoresis [14] or in flow-injection analysis [15]. Their potential instability was attributed to lack of control of the concentrations of the species defining the redox potential at the membrane/metal interface [12,16,17] and their response characteristics were successfully improved by adding an appropriate redox-active component to the PVC membrane [18] or by using an intermediate redox-active polymer layer [19].…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de tudo, algumas dificuldades têm sido encontradas quando da utilização deste tipo de unidades, nomeadamento no que respeita à robustez da membrana e sua selectividade, tendo por isso sido propostas algumas alternativas no sentido de as poder superar. Foi proposto o recurso à fotopolimerização de membranas baseadas em acrilatos 150,225,230,235,239 , originando unidades denominadas "photo-cured electrodes". Este sistema de construção origina membranas sensoras mecanicamente mais fortes e robustas, mais hidrofóbicas, e consequentemente com menores problemas de adesão ao contacto sólido 225 do que os encontrados com a maioria das membranas de PVC.…”
Section: Tipos De Eléctrodos Usados Em Sistemas De Fluxounclassified
“…Solid-contact ISEs, known as coated-wire electrodes (CWEs), were introduced many years ago [4]. However, such electrodes lack long-term stability and they are only useful in specific applications such as chromatographic detectors [5] or in flow-injection analysis [6]. Potential instabilities of CWEs have been mainly attributed to the lack of a well-defined redox couple and the formation of a water layer at the membrane-metal interface [7].…”
Section: Introductionmentioning
confidence: 99%